Irrigation network information system for irrigation area management (Case study in Tapango Polewali District, West Sulawesi). (November 2019) - Faridah, S N; Samsuar,; Sapsal, M T; Suhardi,; Alfiani, S H
Abstract: Success in implement irrigation area management activities is highly dependent on data availability. The existence of a realtime, fast, and accurate information is very important. The data and information needed must be easily accessible to interested parties. Development of an irrigation network information system is carried out by converting data into coordinate form using ArcGIS software. Visual studio software is used to display all data that has been processed. Spatial-based irrigation network information systems built using ArcGIS and Visual Studio software can easily obtain information about channel conditions, rating curves, channel profiles and channel photos. the availability of spatial-based irrigation network information systems facilitates the management of irrigation networks.